Nitrogen doping derived bridging of graphene and carbon nanotube composite for oxygen electroreduction. (23rd August 2021) - Marbaniang, Phiralang; Kapse, Samadhan; Ingavale, Sagar; Thapa, Ranjit; Kakade, Bhalchandra
Summary: In this work, we report a cost‐effective electro‐catalyst for oxygen reduction reaction (ORR) by developing a composite between graphene oxide and carbon nanotubes and simultaneously doping with a nitrogen atom. The nitrogen‐doped carbon nanotube/graphene oxide composites were prepared by chemical oxidation method followed by annealing process. Such composite enhances the active adsorption sites, electrical conductivity and corrosion resistance leading to better impact toward ORR. The N‐graphene oxide/functionalized carbon nanotube catalyst that furnishes both pyridinic‐N and pyridinic‐N‐O (or oxidic‐N) shows higher efficiency toward electrocatalytic ORR performance in alkaline conditions. More interestingly, as‐prepared electrocatalyst shows durability test up to 20 000 potential cycles without loss in its half‐wave potential ( E half ) while commercial Pt/C catalyst shows a huge loss in E half value under similar conditions, indicating sustainability in the performance of former, especially compared to the reported metal or metal‐free electrocatalysts. The origin of high catalytic activity of oxidic‐N is correlated with π‐electron density at the Fermi level studied by density functional theory and considered as an electronic descriptor. Abstract : The combination of N‐doping with bridging in/between GO and fCNT composite gives a synergy effect toward the ORR activity.